DEATH OF BPJS PESIENTS DUE TO SLOW HANDLING BY THE HOSPITAL: (Kematian Pesien BPJS Karena Penanganan Lambat oleh Rumah Sakit) - Lapandewa, Laeko; Rukua, Darwin; Sam, Belinda (Uniqbu Journal of Social Sciences, 2021)
The purpose of this study is to see what the legal consequences are for the late hospital BPJS patients that cause death and whether there are factors that can affect the handling of BPJS participant patients by the hospital. This research includes normative law or doctrinal legal studies, library research or document studies—the Dean of the Law (statute approach), and the conceptual system (conceptual approach). Meanwhile, the abstract approach (conceptual approach) departs from the views and doctrines in the science of law to see which should be implemented or applied with the handling of BPJS participants by the hospital that causes death. The results showed that 1. Following the legal basis of Article 32 letter q of Law no. 44 of 2009 concerning Hospitals, reads: "Every patient has the right: to sue and/or sue the Hospital system. The hospital is suspected of providing services that do not comply with standards, both civil and criminal; In polite terms, the patient can file a lawsuit in court or through a dispute settlement agency against the hospital whose actions have harmed the patient so that the legal consequence of the hospital is the late arrival of the BPJS patient which causes death. In the form of verbal warning; Written warning; or fines and revocation of hospital license. And or take a criminal route by reporting the hospital’s head and/or its health workers to the authorities. 2. In-hospital handling services for BPJS participants information by various factors, including; The level of competence of the hospital apparatus, the quality of the equipment used in the hospital, the organizational culture, the lack of knowledge of BPJS participants about procedures and patients in health care services